Analysis of the β-Glucosidase Family Reveals Genes Involved in the Lignification of Stone Cells in Chinese White Pear (Pyrus bretschneideri Rehd.) - Wang, Han; Zhang, Yingjie; Feng, Xiaofeng; Peng, Fulei; Mazoor, Muhammad Aamir; Zhang, Yang; Zhao, Yu; Han, WenLong; Lu, Jinjin; Cao, Yunpeng; Cai, Yongping (Frontiers in Plant Science, 2022)
BGLU β-glucosidases in the glycoside hydrolase family 1 (GH1) were involved in many processes of plant secondary metabolism. In particular, its de-glycosylation function plays an important role in the transport of lignin monolignols, no comprehensive study of the BGLU family in Chinese pear (Pyrus bretschneideri Rehd.) has been reported. In this study, the 50 BGLU family members from Chinese white pears were identified. Three candidate genes PbBGLU1, PbBGLU15 and PbBGLU16 may involve in lignin synthesis were screened by bioinformatics analysis and qRT-PCR. Subcellular localization showed that all three of these candidate genes were expressed in the extracellular. Then we analyzed the functions of PBBGLU1 and PBBGLU16. In situ hybridization analysis find that PbBGLU1 transcripts were not only localized to some pulp cell walls, lignin deposition and stone cell areas of pear fruit, there was also a small amount of enrichment in normal pear flesh cells, PbBGLU16 transcripts were only enriched in lignin deposition and stone cell areas of pear fruit. Enzyme activity analysis showed that compared with syringin, pGEX4T-1-PbBGLU1 and pGEX4T-1-PbBGLU16 had stronger affinity and faster catalytic efficiency for coniferin. In addition, compared with pGEX4T-1-PbBGLU1, pGEX4T-1-PbBGLU16 shows higher activity and catalytic efficiency for the two substrates. The transformation of PbBGLU1 and PbBGLU16 into Arabidopsis was found that the lignin content of Arabidopsis BGLU-45 mutant, PbBGLU1-RE and PbBGLU16-RE was no change than that of wild-type. However, compared with wild-type Arabidopsis the overexpression plants lignin increased in varying degrees, the effect of PbBGLU16 on the increase of lignin in Arabidopsis is greater than that of PbBGLU1. In pear fruits with transient overexpression of PbBGLU1, the contents of lignin and stone cells in pear fruits were significantly higher (0.01